The Jamaican endemic Exostema orbiculatum belongs to Erithalis (Rubiaceae) - Franck, Alan R.; Lewis, Patrick A.; Oberli, Andreas; Haynes-Sutton, Ann; Rose, Philip E .; Campbell, Keron C. St. E. (Phytotaxa, 2017)
Exostema orbiculatum is transferred to the genus Erithalis based on morphology and ITS sequences, resulting in the new combination Erithalis orbiculata. This species, endemic to west-central Jamaica, is unique in Erithalis for its sessile, orbicular leaves, acuminately spinescent stipules, and sessile inflorescence and flowers.